ULTRASOUND AS TOOL FOR DIAGNOSIS OF DISEASES OF THE REPRODUCTIVE TRACT BULLS - Sousa, K C; Rolim Filho, S T; Ribeiro, Haroldo Francisco Lobato; do Vale, William Gomes (Archives of Veterinary Science, 2015)
Abstract The purpose of this study was to evaluate by ultrasound and breeding soundness examination (BSE) the major diseases affecting the reproductive system of Nelore bulls, bred extensively in the state of Para, Brazil. Fifty-nine pure Nelore bulls were used, aged between 5 to 10 years, raised extensively in a commercial farm in the municipality of Paragominas, Pará state, Brazil. Scrotal circumference, testicular length and width were measured. Semen collection for evaluation of ejaculate volume, turbulence, motility, vigor, concentration and sperm pathologies was performed. Ultrasound examination was performed by equipment type Ultrasonic Transducer - CHISON/D600vet, linear transducers, where the frequency used was 5 MHz, being held two images of each testis, the longitudinal-lateral, lateral and transverse planes. The images were processed using the program Image J. The data were analyzed using the statistical program SAS (2000) and means were compared using Tukey’s test (p < 0.05). Among the fifty-nine bulls evaluated, 39 (66.1%) were classified as suitable for breeding and 20 (33.8 %) were classified as unsuitable. Throughout the use of ultrasonography changes as testicular degeneration one case (1.6%), one of orchitis (1.6%) , one of hydrocele (1.6%), nine of calcification (15.2%) and two cysts in the testicular region parenchyma (3.3%) were found. The average scrotal circumference was 38.6±2.4 and 40.4±3.6 cm for the animals fit and unfit for reproduction categories respectively, observing statistical difference (P < 0.05). The average physical characteristics of semen for breeding animals was 74.2±18.8% for motility, 2.9±1.62% for wave motion, 3.2±1.08% for vigor, 4.7 ± 2.58 mL for volume, 0.84 ± 0.56 x106 sperm/mm3 concentration and 9.4±4.7% of total sperm pathologies. For the unfit animals data was 73.2±24.6% for motility, 2.8±1.78% for wave motion, 3.3±1.17 vigor , 4.5 ± 2.16 mL volume , 27±0.14 % of total sperm pathologies and 0.85±0.51 x 106 sperm/mm3 for concentration. Statistical differences in the percentage of total sperm pathologies between fit and unfit animals was observed (P<0.05). The mean pixel intensity of testicular parenchyma was 45.35 to 45.25 for fit for animals unfit animals, without any statistical difference (P>0.05). Thus, it can be concluded that ultrasonography is an essential complementary tool in the diagnosis of reproductive disorders in animals subjected to BSE and its use should be recommended.